2010
DOI: 10.1242/jeb.033662
|View full text |Cite
|
Sign up to set email alerts
|

Fuel switching and energy partitioning during the postprandial metabolic response in the ball python (Python regius)

Abstract: SUMMARYDigestion, absorption and assimilation of the meal are active processes that require start-up energy before the energy contained in a meal can be utilized. The energetic costs associated with feeding (specific dynamic action, SDA) are high in sit-and-wait foraging snakes that tolerate long fasting periods. We used 13 C-labelled prey to partition between endogenous energy sources (i.e. snakes own resources) and exogenous energy sources (i.e. prey). A linear mixing model was then applied to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…This targeted (sensu isotopic labeling of the protein and lipid pools in the mice allows us to quantify the different oxidative fates of these nutrients. Starck et al (2004) and Waas et al (2010) fed pythons with 13 C-enriched mice and observed peak δ 13 C at 48 h. Although they did not directly measure the δ 13 C in the protein and lipid pools of those mice, they likely had roughly the same δ 13 C-enrichment (Guzman et al, 2015). It follows that this 48 h time point represents cumulative oxidation of both proteins and lipids in the meal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This targeted (sensu isotopic labeling of the protein and lipid pools in the mice allows us to quantify the different oxidative fates of these nutrients. Starck et al (2004) and Waas et al (2010) fed pythons with 13 C-enriched mice and observed peak δ 13 C at 48 h. Although they did not directly measure the δ 13 C in the protein and lipid pools of those mice, they likely had roughly the same δ 13 C-enrichment (Guzman et al, 2015). It follows that this 48 h time point represents cumulative oxidation of both proteins and lipids in the meal.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study Waas et al (2010) fed mice raised on corn-based diets to pythons. They collected the breath at 30 min intervals during the first 12 h of digestion (and then hourly over the following 2 days) and found that the δ 13 C increased within 4 h of ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented the magnitudes and time courses of changes in exhaled δ 13 C resulting from exogenous sources, namely experimental diet switches whereby a human (Schoeller et al, 1980;Gay et al, 1994;Tanis et al, 2000) or another animal (Perkins and Speakman, 2001;Ayliffe et al, 2004;Carleton et al, 2006;Welch et al, 2006Welch et al, , 2008Voigt and Speakman, 2007;Voigt et al, 2008;Waas et al, 2010) is switched from a diet chiefly derived from C3 plants to one derived from C4 plants, or vice versa. Unfortunately, these experiments cannot inform us about the changes in the δ 13 C of exhaled carbon dioxide when animals experience endogenous changes in oxidative substrates.…”
Section: Endogenous and Exogenous Causes For Changes In The δ 13 C Inmentioning
confidence: 99%
“…We believe that the inability for researchers to arrive at a consensus regarding this issue stems from differences in experimental design (e.g., different levels of exercise intensity and the lack of non-exercising 'control' treatments), unstandard reporting practices (e.g., particularly with respect to δ 13 C), small sample sizes (e.g., usually below n = 8), and sparse sampling frequencies (e.g., usually 15-to 30-minute intervals). Understanding the naturally occurring changes in δ 13 C that occur in the breath during elevated metabolic states is clearly important for studies of human energetics, but also for the rapidly growing use of 13 C-breath testing in comparative physiology (e.g., Hatch et al, 2002;Welch et al, 2006;Voigt and Speakman, 2007;Welch and Suarez, 2007;Waas et al, 2010;Voigt et al, 2012).…”
Section: Endogenous and Exogenous Causes For Changes In The δ 13 C Inmentioning
confidence: 99%
“…Research into the SDA of vertebrates known to digest relatively large meals at relatively infrequent intervals has revealed that SDA is fuelled using a mixture of endogenous and exogenous nutrients (Starck et al, 2004;Waas et al, 2010), but those studies were not able to identify which classes of nutrients (e.g. carbohydrates, lipids and amino acids) provided this energy.…”
Section: Introductionmentioning
confidence: 99%